Pengaruh Brand Image terhadap Brand Loyalty dengan Brand Trust sebagai Variabel Mediasi dan Brand Love sebagai Variabel Moderasi (Studi pada Starbucks Coffee di Daerah Jakarta) - Setyaningsih, Yanti; Rita Amelinda (Jurnal Ekonomi, Manajemen dan Perbankan (Journal of Economics, Management and Banking), 2026)
This study was conducted with the aim of analyzing the effect of Brand Image on Brand Loyalty by testing the effect of Brand Trust as a mediating variable and Brand Love as a moderating variable on Starbucks Coffee customers in the Jakarta area. In analyzing the aspects that retain Starbucks' loyal customers, the researcher conducted a test by reviewing the strength of Starbucks' branding that can lead to Brand Loyalty. The research method used a quantitative approach through purposive sampling, using a sample of 327 respondents who were loyal customers of Starbucks Coffee in the Jakarta area. This study used WarpPLS 8.0 software to test the data and perform SEM analysis. The results showed that Brand Image had a positive and significant effect on Brand Loyalty. Brand Image also had a positive effect on Brand Trust. However, Brand Trust does not have a positive and significant effect on Brand Loyalty, either through direct influence or as a mediating variable. Furthermore, Brand Love positively and significantly moderates the relationships between Brand Image and Brand Loyalty, as well as between Brand Trust and Brand Loyalty. So, this study has implications that companies can focus on maintaining their brand image and brand love, as well as reviewing aspects other than Brand Trust in increasing Brand Loyalty, so that companies can be sustainable in the long term.